Innate Immune Reconstitution in Humanized Bone Marrow-Liver-Thymus (HuBLT) Mice Governs Adaptive Cellular Immune Function and Responses to HIV-1 Infection - Garcia-Beltran, Wilfredo F.; Claiborne, Daniel T.; Maldini, Colby R.; Phelps, Meredith; Vrbanac, Vladimir; Karpel, Marshall E.; Krupp, Katharine L.; Power, Karen A.; Boutwell, Christian L.; Balazs, Alejandro B.; Tager, Andrew M.; Altfeld, Marcus; et al. (Frontiers in Immunology, 2021)
Humanized bone marrow-liver-thymus (HuBLT) mice have facilitated the study of human immune function and human-restricted pathogens, including human immunodeficiency virus type 1 (HIV-1). These mice not only support robust HIV-1 infection, but also uniquely harbor long-term in vivo development of HLA-restricted human T cells and recapitulate many aspects of acute and chronic HIV-1 pathogenesis. However, HuBLT mice challenged with HIV-1 exhibit variable T-cell responses across individual mice, hindering the ability to confidently detect HIV-1–specific responses or vaccine-associated effects. To understand the source of this variability, we comprehensively analyzed T-cell development, diversity, and priming in HuBLT mice. We found that while T-cell diversity, thymic development, and differentiation appeared intact in HuBLT mice, there was a defect in T-cell function, polarization, and priming that correlated with poor reconstitution of innate immune cells, particularly monocytes. While virtually all HuBLT mice were well-reconstituted with T and B cells, there was variable reconstitution of monocytes that positively correlated with T-cell function as well as TH1 polarization. Monocyte reconstitution also positively correlated with CD8+ T-cell responses in vivo during acute HIV-1 infection and the selection of viral variants. Thus, despite proper T-cell reconstitution, a deficiency in innate immune reconstitution in HuBLT mice hinders the development of more robust antigen-specific T-cell responses, which if improved would enhance the model’s ability to better recapitulate human adaptive immunity.